2016
DOI: 10.3892/ol.2016.5521
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β activates focal adhesion kinase and Src to induce matrix metalloproteinase-9 production and invasion of MCF-7 breast cancer cells

Abstract: Abstract. Interleukin-1β (IL-1b) is a pleiotropic cytokine that is important in tumor progression and invasion. Matrix metalloproteinase-9 (MMP-9), which is a secreted matrix-degrading enzyme, is one of the key regulators of tumor invasion and metastasis. The current report indicated that IL-1b promotes MMP-9 production and cell invasion in non-metastatic MCF-7 breast cancer cells. IL-1b activated focal adhesion kinase (FAK) and proto-oncogene tyrosine-protein kinase Src (Src). Moreover, inhibiting the Src/FAK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 38 publications
1
37
0
1
Order By: Relevance
“…Intriguingly, there were no significant changes in total c-Src expression levels or its phosphorylation status by PTP4A2 knockdown (36). Src activation induces Snail and MMP-9 expression (37,38). In this study, miR-1271 inhibited the phosphorylation of c-Src at Tyr416 (Y416), and Snail and MMP-9 expression.…”
Section: Discussionmentioning
confidence: 59%
“…Intriguingly, there were no significant changes in total c-Src expression levels or its phosphorylation status by PTP4A2 knockdown (36). Src activation induces Snail and MMP-9 expression (37,38). In this study, miR-1271 inhibited the phosphorylation of c-Src at Tyr416 (Y416), and Snail and MMP-9 expression.…”
Section: Discussionmentioning
confidence: 59%
“…FF at 1 Pa activated Src, while FF at 0.25 Pa inactivated Src. Growth factors can activate Src, 41 and we observed that TGFβ1 was upregulated by FFCM at 1 Pa and downregulated by FFCM at 0.25 Pa. Snail expression was also altered by FFCM in a shear stress intensitydependent manner.…”
Section: Load-dependent Regulation Of Serum Tgfβ D-dimer and Cholesmentioning
confidence: 62%
“…FAK localizes to sites of transmembrane integrin receptor clustering, and facilitates intracellular signaling events and cell migration (Sieg et al, ; Thakur et al, ). JNK and FAK also signal via CXCR4 and MMP family to facilitate intracellular signaling and cell migration (Liao et al, ; Mon et al, ). We found that hypoxia enhanced JNK and FAK phosphorylation, and STAT3 inhibition suppressed JNK and FAK phosphorylation.…”
Section: Discussionmentioning
confidence: 99%